체제전환국의 농업금융제도 개혁과 시사점 - 박준기 (한국농촌경제연구원, 2003)
Lessons from the Changes of Agricultural Financial Systems in Transition Countries Financial stability and sound systems and institutions to provide access to credit, are indispensable sustainable development of a agricultural sector. The purpose of this study is to explore the problems of financing the agricultural sector during the transitionary period and the lessons from the changes of agricultural financial systems in transition countries - especially focused on the cases of Central Eastern European Countries and China. The macroeconomic instability in the transition countries affected the profitability of the agricultural sector though increasing uncertainties and risks created by inflation, supply of inputs, and shortage in credit supply. It undermines existing financial institutions and damages confidence in government policies and agricultural banking system. In the transition countries, the agricultural sector suffered from the limited funds available that were additional, more acute, problems than the other sectors, although problems may differ significantly between countries. First, producers had difficulties in providing and valuing collateral for loans because of the lack of clear property rights and the incomplete land reform. This hampered the level of private investment in agricultural sector and retarded the development of the capital markets. Second, farmers faced the problems with collateralization of the loans. Banks often refused agricultural land as collateral because of the absent of a land market, the incomplete land reform, or too low land prices. Third, costs for monitering and screening loans were too high during the transition. Fourth, large bad debts had been accumulated in the agricultural sector. Indebtedness inhibited the incentives for better management, the provision of new loans, and the process of land restitution and restoration of property rights. Fifth, farm incomes had fallen in the transition period because of worsening terms of trade, i.e., rising input prices and declining output prices. Farmers had difficulties to sell their products due to a stagnation of the domestic markets and the collapse of the trading system. These problems resulted in severe credit constraints for the agricultural sector during transition. The credit constraints imposed high costs in terms of rural poverty, distortion of production, and liquidation of assets. Governments attempted to overcome these problems by establishing special financial institutions, subsidizing credit, setting up credit guarantee funds, stimulating institutional innovations, and investing in human capital and retraining programmes. Specialized agricultural credit institutions were established to provide the effective financial service to agricultural sector. The most important advantages of the institutions were lower transaction, monitoring and verification costs through greater specialist knowledge of relevant agricultural activities. But the disadvantages of these institutions were their higher portfolio risk due to their specialization and put under government control. Subsidized credit and loan guarantees also were used in many transition countries. Loan guarantees could be effective in stimulating lending to agriculture in the short term, as long as they are designed to maintain repayment incentives and it were seen as less distortional than subsidized credit and could encourage greater participation by commercial banks. Bad debts of producers inherited from the centrally-planned period. Although the debts were not accumulated under market economy, it was obvious that the market couldn't solve this historic problem. Most governments of the transition countries converted the bad debts into state debt. This study also tried to suggest the short- and mid-term direction of agricultural financial reform in the transition period of North Korea, if possible. The agricultural financial reforms in transition countries were showed the problems and possible solutions of providing credit to the agricultural sector. When North Korea will decide on agricultural financial reform and manage the reform process, it will be necessary for North Korea to obtain know-how from the cases of transition countries. In particular, lacking experience and self-confidence, North Korea will need helps from outside at the beginning stages of the reform. The lessons from the preceded transition countries will help North Korea take more active reform measures and establish a successful agricultural financial system. Researcher: Park Joon-Kee and Park Seong-Jae E-mail address: jkpark@krei.re.kr
Keywords: 체제전환국 농업금융 거시경제동향 일반금융개혁